2020
DOI: 10.21203/rs.2.17892/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recovery and stable persistence of chloroquine sensitivity in Plasmodium falciparum parasites after its discontinued use in Northern Uganda.

Abstract: Background Usage of chloroquine was discontinued from the treatment of Plasmodium falciparum infection in almost all endemic regions because of global spread of resistant parasites. Since the first report in Malawi, numerous epidemiological studies have demonstrated that the discontinuance led to re-emergence of chloroquine-susceptible P. falciparum parasites, suggesting a possible role in future malaria control. However, most studies were cross-sectional, with few studies looking at the persistence of chloroq… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…falciparum revision to chloroquine sensitivity as documented recently in different parts of Sub-Saharan Africa. The revision to parasites with wild type pfmdr1 and pfcrt alleles sensitive to chloroquine and amodiaquine [ 78 80 ] is a great advantage to ASAQ.…”
Section: Discussionmentioning
confidence: 99%
“…falciparum revision to chloroquine sensitivity as documented recently in different parts of Sub-Saharan Africa. The revision to parasites with wild type pfmdr1 and pfcrt alleles sensitive to chloroquine and amodiaquine [ 78 80 ] is a great advantage to ASAQ.…”
Section: Discussionmentioning
confidence: 99%
“…The significant increase in pfmdr1 N86 wild-type from 59.5% to 91.4% in the three years to 2020 also suggests the potential resurgence of chloroquine sensitivity. Although this phenomenon has been widely observed in African countries [13][14][15], it is very rare in SEA [41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the issue of ART resistance, previous ex vivo drug study also found that most P. falciparum parasites were resistant to chloroquine despite the discontinuation of chloroquine use in the early 2010s [12]. This is contrary to the observations in many African countries where chloroquine susceptibility recovered years after discontinuation [13][14][15].…”
mentioning
confidence: 92%
“…In this regard, studies carried out in P. falciparum suggest that CQ-wildtype alleles in pfmdr1 and pfcrt have a selective advantage over resistant genotypes when CQ pressure is not exerted [45][46][47]. In this regard, regions where CQ was discontinued experienced an increase of wildtype pfcrt and pfmdr1 P. falciparum strains [45,46,48]. However, this is unlikely to happen with the P. vivax population in the Peruvian Amazon due to the continued use of CQ as first-line treatment.…”
Section: Discussionmentioning
confidence: 99%